To Fire or to Hoard? : Explaining Japan's Labor Market Response in the Great Recession - Steinberg, Chad (IMF Working Papers; Working Paper, 2011)
The Great Recession pushed Japan's unemployment rate to historic highs, but the increase has been small by international standards and small relative to the large output shock. This paper explores Japan's cyclical labor market response to the global financial crisis. Our findings suggest that: (i) employment responsiveness has been historically low but rising over time with the increasing importance of the non-regular workforce; (ii) the labor market response was consistent with historical patterns once we control for the size of the output shock; and (iii) the comparatively lower employment response vis-a-vis other countries can in part be explained by the quick implementation of an employment subsidy program, a more flexible wage system, and a corporate governance structure that places workers rights above shareholders.